Police ethics: the corruption of noble cause - Caldero, Michael A. (Routledge, 2018)
Value-based decisionmaking and the ethics of noble cause -- Value-based decisionmaking : understanding the noble cause -- Values, hiring, and early organizational experiences -- Values and administrative dilemmas -- The social psychology of cops' values -- Noble-cause corruption -- From economic to noble-cause corruption -- Stress, organizational accountability, and the noble cause -- Ethics and the means-ends dilemma -- Police culture, ends-orientation, and noble-cause corruption -- Ethics and police in a time of change -- Policing citizens, policing communities : toward an ethic of negotiated order -- The stakes -- Recommendations -- Conclusion: the noble cause